Overview of patents deposited in Brazil: an analysis from the largest patent depositors in the Derwent Innovations Index base - Moura, Ana Maria Mielniczuk de; Gabriel Junior, Rene Faustino; Magnus, Ana Paula Medeiros; Santos, Fernanda Bochi; Scartassini, Verônica Barboza (Faculdade de Filosofia e Ciências, 2019)
The patentes documents constitue an importants informations sources, in addiction to their industrial and economy relevance. The presente study analyzes the patent deposit in Brazil, based on verification of the largest depositor of patent indexed in the Derwent Innovations Index from 2004 to 2016. The study is qualitative with descriptive character, its corpus is formed by the records of patents deposited in Brazil that were indexed in the database Derwent Innovations Index in the period highlighted. The research was performed with temporal delimitation from 2004 to 2016 and result in a total of 208.064 records. Data collection was performed in March 2017 and with the records collected a database exported to a MySQL database was created. To analyze and measure the collected data, Excel software, Thesa and Vosviewer were used to standardize the name of the institutions patent applicants, analysis and presentantion of the results. Throughout the study, there was a predominance of multinational corporations in the largest filing of patents in Brazil, related to the areas of health, information technology and electronics.